2016
DOI: 10.1111/cfs.12306
|View full text |Cite
|
Sign up to set email alerts
|

‘She was like a mother and a father to me’: searching for the ideal mentor for youth in care

Abstract: Recent studies of youth in out‐of‐home placements have indicated that a successful mentoring relationship in care is associated with better emotional, educational and behavioural outcomes in adulthood. The goal of this exploratory qualitative study is to describe the profile of a staff member who is able to establish a meaningful relationship with youth in care through the perspectives of 20 young adults aged 21–26 who left care in Israel. Findings revealed that the staff member who formed meaningful relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
1
22
0
2
Order By: Relevance
“…The young adults' former counselors were also the ones with whom they stayed in contact years after leaving care. Staff's important role in the lives of youth in care was evident in earlier studies, both as a type of social support and as mentors serving as role models in addition to or as substitutes for their parents (Ahrens, DuBois, Richardson, Fan, & Lozano, 2008;Greeson, Usher, & Grinstein-Weiss, 2010;Sulimani-Aidan, 2016). However, compared with other countries, the unique organizational structure of educational settings in Israel leads to a much more dominant role of the social counselors, as our findings suggest.…”
Section: Relationship With Staff In Care and After Emancipationsupporting
confidence: 55%
See 1 more Smart Citation
“…The young adults' former counselors were also the ones with whom they stayed in contact years after leaving care. Staff's important role in the lives of youth in care was evident in earlier studies, both as a type of social support and as mentors serving as role models in addition to or as substitutes for their parents (Ahrens, DuBois, Richardson, Fan, & Lozano, 2008;Greeson, Usher, & Grinstein-Weiss, 2010;Sulimani-Aidan, 2016). However, compared with other countries, the unique organizational structure of educational settings in Israel leads to a much more dominant role of the social counselors, as our findings suggest.…”
Section: Relationship With Staff In Care and After Emancipationsupporting
confidence: 55%
“…For example, retrospective studies showed that all young adults who left care had staff members with whom they had formed a meaningful relationship (Sulimani-Aidan, 2016). In addition, separation from staff was perceived as one of the most difficult challenges in transition from care to independent living (Sulimani-Aidan, 2014).…”
Section: Staff In Residential Settings In Israelmentioning
confidence: 99%
“…For mentoring to be successful, it is desirable for mentors to have a good understanding of their mentees' actiotopes, which include the mentee, their environment, and their interactions with their environment. 64,70,71 Mentors need to have an overview of which relevant processes are already regulated with regard to the mentoring objectives and how well these processes are orchestrated. In other words, they need to know which activities within the actiotope of their mentees form a functional regulatory network of processes to reach the mentoring objectives.…”
Section: Regulatory Networkmentioning
confidence: 99%
“…Although the presence of a mentor has been established as possibly promoting better outcomes after emancipation (Sulimani‐Aidan, ), most previous mentoring studies examine only specific aspects of the mentoring relationships. According to mentoring theory, the process of creating positive change in the youths' lives involves mentors serving different functions in the relationship and acting as parental figures, role models, and life coaches (Ahrens et al, ; Greeson et al, ; Greeson & Bowen, ; Sulimani‐Aidan, , ). Thus far, no study has explored the differential contribution of each of the documented mentoring functions in relation to the life skills of youth in care.…”
Section: Mentoring Characteristicsmentioning
confidence: 99%
“…The mentoring literature suggests that different components in the mentoring process including quality, longevity, and type of relationships (natural vs. assigned mentor) play a role in their effectiveness (Ahrens et al, ; Greeson et al, ; Rhodes, Spencer, Keller, Liang, & Noam, ; Sulimani‐Aidan, , ). However, earlier studies that examined the relationship between mentoring and outcomes among youth in care included only some of the dimensions of the relationships (e.g., specific function and duration) rather than the various array of characteristics that define these relationships.…”
Section: Introductionmentioning
confidence: 99%